Comparing Marginal Fitness between Overdenture Copings Produced by Three Techniques - Yaman Aahed Alhamamy; Ahmed Al-Ali (University of Mosul, College of Dentistry, 2023)
Aims: to compare the marginal fit of copings produced by Direct Metal Laser Sintering (DMLS), Hard metal CAM (Computer Assisted Milling), and conventional casting techniques. Materials and Methods: An implant abutment was used as ideal model which was scanned by 3D scanner and 8 copings of each group were fabricated from a single STL file. Each specimen was cross-sectioned into two halves and 2 points on each half were measured with digital microscope and image processing software, Readings were statistically analyzed with ANOVA test and Duncan's multiple range test. Results: Significant difference was found between the groups in both marginal and internal gaps. The hard metal milling group showed significantly smaller gaps than the other two groups, while no significant difference was found in fit between DMLS and conventional casting groups Conclusions: within the limitations of this study, hard metal milled copings were found to have the superior fit compared to the other two groups, however, all copings in all three groups were found to have gaps within the clinically acceptable range of marginal fitness.